Expression of m6A Regulators Correlated With Immune Microenvironment Predicts Therapeutic Efficacy and Prognosis in Gliomas - Xu, Shengchao; Tang, Lu; Dai, Gan; Luo, Chengke; Liu, Zhixiong (Frontiers in Cell and Developmental Biology, 2020)
Background: N6-methyladenosine (m6A) RNA methylation and tumor immune microenvironment played crucial roles in cancer development. However, their association in gliomas remains to be fully elucidated. Methods: A total of 1,018 glioma patients extracted from CGGA database were enrolled in our study, in which 325 were set as the training cohort and 693 were defined as the validation cohort. Survival differences evaluated by Kaplan-Meier analysis between groups. Patients were clustered into subgroups by consensus clustering. ESTIMATE algorithm was applied to calculate immune and stroma scores. The infiltration of immune cells was characterized by TIMER algorithm. The risk signature was constructed by multivariate Cox regression analysis. Results: Nineteen m6A regulators were highly expressed in glioma tissues. The expression of m6A regulators was associated with prognoses, grade, isocitrate dehydrogenase (IDH) status, and 1p19q status of gliomas. Two subgroups were identified by consensus clustering, in which cluster 1 was associated with favorable prognosis, high stroma and immune scores, and high immune infiltration. After the construction of risk signature in the training cohort, patients in the high risk group suffered from poor prognoses, high stroma and immune scores, and high immune infiltration. The risk signature was verified in the validation cohort, which exhibited consistent results. Besides, the copy number alternations of risk signature genes dynamically affect the infiltration of immune cells. Moreover, patients in low risk group enjoyed better prognoses without chemoradiotherapy or single chemotherapy. Conclusions: Our study revealed that m6A regulators could predict the prognosis and therapeutic efficacy, and were also associated with the immune microenvironment in gliomas.